2018
DOI: 10.1007/s13201-018-0680-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of microspheric Fe(III)-ion imprinted polymer for selective solid phase extraction

Abstract: In this research work, an Fe(III)-IIP was prepared using methacrylic acid as monomer, divinylbenzene as cross-linker, azobisisobutyronitrile as initiator. The ion imprinted polymer was functionalized with Fe(III)8-hydroxy quinolone complex under thermal conditions by copolymerization with the monomer and the cross-linker. The prepared Fe(III)-ion imprinted polymer (IIP) and non-ion imprinted polymer (Non-IIP) were characterized with fourier transform-infrared spectroscopy, scanning electron microscopic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…126 The conventional iron extraction technologies include the solvent extraction, which has been reported in various literatures investigated with neutral extracts, like ketones, amines, ethers, etc., but neutral extracts are linked with some disadvantages like slow kinetics and need high mineral acid quantities for the recovery of iron. Keeping these problems in focus, Ara et al 127 demonstrated an ionimprinted polymer technique derived by thermal copolymerization of the complex of Fe(III), MAA, and divinyl benzene. The target of this study is to offer a process which can completely remove the Fe(III) from a mixture of solution and then can be applied to practicality.…”
Section: Adsorption Of Heavy Metal Ions By Using Mipsmentioning
confidence: 99%
See 1 more Smart Citation
“…126 The conventional iron extraction technologies include the solvent extraction, which has been reported in various literatures investigated with neutral extracts, like ketones, amines, ethers, etc., but neutral extracts are linked with some disadvantages like slow kinetics and need high mineral acid quantities for the recovery of iron. Keeping these problems in focus, Ara et al 127 demonstrated an ionimprinted polymer technique derived by thermal copolymerization of the complex of Fe(III), MAA, and divinyl benzene. The target of this study is to offer a process which can completely remove the Fe(III) from a mixture of solution and then can be applied to practicality.…”
Section: Adsorption Of Heavy Metal Ions By Using Mipsmentioning
confidence: 99%
“…Reaction mechanism of Fe­(III)-IIP by using an 8-hydroxyquinoline complex (figure credit: Springer-Nature 2018, distributed under Creative Commons CC-BY).…”
Section: Adsorption Of Heavy Metal Ions By Using Mipsmentioning
confidence: 99%
“…However, these sorbents have been used mostly for Fe(II) or Fe(III) enrichment; their application for Fe(II)/Fe(III) speciation has not been tested. Only Roushani et al ., 17 Ara et al 20 . and Saatçilar et al 21 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Choosing the right functional monomer and ligand is a key factor that determines the stability of the complex formed before and during the polymerization process as well as the subsequent ability of the IIP to interact selectively with the target ion. According to the available literature, there are studies on new IIPs and their application for SPEs of Fe(II) 10 and Fe(III) [11][12][13][14][15][16][17][18][19][20] ions. However, these sorbents have been used mostly for Fe(II) or Fe(III) enrichment; their application for Fe(II)/ Fe(III) speciation has not been tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation